Seroprevalence of Antibodies Against Anaplasma Phagocytophilum and Borrelia Burgdorferi in Horses (Equus Caballus) from Northern Algeria - Laamari, Abdelouahab (J Vet Res, 2020)
INTRODUCTION: Horses (Equus caballus) are susceptible to tick-borne diseases. Two of them, Lyme borreliosis due to Borrelia burgdorferi and granulocytic anaplasmosis due to Anaplasma phagocytophilum were investigated in Algerian horses. The diseases have been less extensively studied in horses and results pertinent to Algeria have not been published. MATERIAL AND METHODS: Blood samples were obtained from 128 horses. IgG antibodies directed against Anaplasma phagocytophilum and Borrelia burgdorferi were detected by an indirect immunofluorescence antibody test (IFAT) and ELISA. The potential effects of age, gender, breed, and health status on seropositivity were also evaluated. RESULTS: Using IFAT, 28 (21.8%) and 25 (19.5%) animals were positive for B. burgdorferi and A. phagocytophilum, respectively. Using ELISA, 19 (14.8%) and 33 (25.9%) animals were positive for these bacteria. CONCLUSION: The study shows that horses in Algeria are exposed or co-exposed to tick-transmitted zoonotic bacterial species.